A Velvet Empire: French Informal Imperialism in the Nineteenth Century - Todd, David (Princeton : Princeton University Press, 2021)
"After Napoleon's downfall in 1815, France embraced a mostly informal style of empire, one that emphasized economic and cultural influence rather than military conquest. A Velvet Empire is a new global history of French imperialism in the nineteenth century, providing new insights into the mechanisms of imperial collaboration that extended France's power from the Middle East to Latin America and ushered in the modern age of globalization"-- Provided by publisher.
5. Agents of informal empire: French expatriates and extraterritorial jurisdiction in Egypt.
Includes bibliographical references (pages 287-329) and index.
Keywords: France--Foreign relations--19th century; France--Politics and government--19th century